FREQUENCY OF PRETERM DELIVERIES IN PATIENTS WITH HYPERTENSIVE DISORDER OF PREGNANCY (The Research of Medical Science Review, 2025)
OBJECTIVE: To determine the frequency of preterm deliveries among patients diagnosed with hypertensive disorders of pregnancy and assess associated maternal characteristics and risk factors. METHODOLOGY: A descriptive cross-sectional study was conducted at JPMC, Karachi, on 97 pregnant women (18–40 years) with hypertensive disorders of pregnancy, selected through non-probability consecutive sampling. Inclusion criteria included singleton pregnancies (≥28 to <37 weeks), while women with multiple gestations, diabetes, cardiac disease, or those unwilling to consent were excluded. Preterm delivery (<37 weeks) was confirmed via ultrasound. Data was analyzed using SPSS 26, with p < 0.05 considered statistically significant. RESULTS: Among 97 women with hypertensive disorders of pregnancy, preterm delivery occurred in 34 (35%) cases. The mean maternal age was 26.32 ± 5.24 years. Younger age (18–26 years: 73.5% vs. >26 years: 26.5%, OR: 2.691, p = 0.030) and booked status (50.0% vs. 27.0%, OR: 2.706, p = 0.023) were significantly associated with preterm birth, while BMI, parity, mode of delivery, and socioeconomic status showed no significant impact. Eclampsia was more prevalent in preterm deliveries (26.5% vs. 9.5%), though not statistically significant. CONCLUSION: The findings of current study reported that there is a strong correlation between hypertension disorder of pregnancy and early birth, with gestational hypertension, preeclampsia, or eclampsia as the most common types. Younger mothers and booking status were significant factors. This highlights the roles of screening, awareness, and intervention, additional to the mitigation of preterm birth risk and improved maternal and neonatal outcomes.